Design of Artificial Red Blood Cells using Polymeric Hydrogel Microcapsules: Hydrogel Stability Improvement and Polymer Selection. Issue 10 (October 2016) - Zhang, Wujie; Bissen, Matthew J.; Savela, Emily S.; Clausen, Joshua N.; Fredricks, Samantha J.; Guo, Xiaoru; Paquin, Zachary R.; Dohn, Ryan P.; Pavelich, Ian J.; Polovchak, Alec L; Wedemeyer, Michael J.; Shilling, Brock E.; et al.
Purpose: To improve the stability of pectin-oligochitosan hydrogel microcapsules under physiological conditions. Methods: Two different approaches were examined: change of the cross-linker length and treatment of the hydrogel microcapsules with 150 Mm CaCl2 . Replacement of pectin with alginate was also studied. Results and Conclusions: It was observed that the molecular weight of the cross-linker oligochiotsan had no significant improvement on microcapsule stability. On the other hand, the treatment of pectin-oligochitosan microcapsules with Ca 2+ increased the microcapsule stability significantly. Different types of alginate were used; however, no red-blood-cell-shaped microcapsules could be produced, which is likely due to the charge-density difference between deprotonated pectin and alginate polymers.